Tradiciones culturales y su aporte turístico al desarrollo de la ciudad de Babahoyo - Mejía Bajaña, Carla Paola (2020)
This study focuses on cultural traditions and their tourist contribution to the development of the Babahoyo City, this being an agricultural area with numerous socio-cultural and religious activities celebrated throughout the year. For the collection of the information, this study was based on the qualitative and quantitative design through documented, diagnostic and descriptive research supported by the survey, interview and observation techniques, which helped determine the current situation, determining that there is a waste of the tributary, since it is not used to boost tourism. Due to this, it was concluded that this resource should be used since river tourism since it is proven around the world that it is a dynamic activity